Businesses and Human Rights: Regional Approaches - Guevara Duque, Diana María (Iuris Dictio, 2022)
Transnational corporations (TNCs) have great political, economic, and legal power around the world, supported by a structure that protects their interests, situation that is clearer when TNCs"™ activities have adverse impacts on human rights. This has been proven in cases such as Chevron and its effects in the Ecuadorian Amazon region, or the collapse of the Rana Plaza building in Bangladesh in 2013. Against this background, the international community recognized the need to fill the legal vacuum in regard to TNCs"™ activities, and two main frameworks were created. First, the Norms on the Responsibility of TNCs and other Business Enterprises with regard to Human Rights (2003), which were never formally adopted; and the Guiding Principles on Business and Human Rights (UNGPs) (2011), which are strictly voluntary. Afterwards, in 2014, the UN Human Rights Council acknowledged the indispensability of a legally binding instrument regarding human rights and TNCs, therefore, creating a specialized working group for this purpose. The aforementioned efforts are part of the International System, which raises the following questions: Are regional bodies addressing this issue? Do any of the regional human rights instruments have dealt with it in any way? The focus of this paper will be to compare and contrast existent human rights regulations related to transnational corporations"™ impact on human rights, focused on the European and the Inter-American regional systems.